Adult‐onset Niemann–Pick disease type C masquerading as spinocerebellar ataxia. Issue 4 (22nd February 2022) - Vo, Mary L.; Levy, Tess; Lakhani, Shenela; Wang, Chengbing; Ross, M. Elizabeth
Abstract: Background: Adult‐onset Nieman–Pick disease type C (NPC) is a rare progressive ataxia caused by lysosomal accumulation of unesterified cholesterol resulting in severe disability and death. The diagnosis of NPC can be challenging as clinical features overlap with other more common hereditary ataxias. This study pursued the molecular genetic basis of adult‐onset cerebellar ataxia manifesting in two siblings. A prior diagnosis of spinocerebellar ataxia type 2 (SCA2) based on an ataxia gene panel was questioned when the younger sibling developed similar symptoms but had discordant genetic results. Methods: Neurologic examination, whole exome sequence (WES), targeted sequence to establish genome phasing, and cytochemical and biochemical studies of fibroblast cultures were employed. Results: The pedigree and neurological examinations suggested a recessive or possibly dominant cerebellar ataxia. WES showed the siblings were both compound heterozygous for two rare variants in the NPC1 gene—one pathogenic, stop gain at p.Arg934Ter (NM_000271.4), and a missense change, p.Pro471Leu (NM_000271.4), of uncertain significance. Filipin staining of fibroblast cultures showed lysosomal cholesterol accumulation and biochemical assay demonstrated impaired cholesterol esterification. Conclusions: The study established the correct molecular diagnosis of biallelic, adult‐onset NPC in a patient initially diagnosed with SCA. Additionally, the p.Pro471Leu variant was identified as likely pathogenic. Inaccurate molecular diagnosis will deprive NPC patients of treatment options. Investigation using WES is justified when a detected expansion size is in the borderline range for pathogenicity. Abstract : We present a sibling pair who were initially diagnosed with adult‐onset spinocerebellar ataxia Type 2 based on borderline repeat expansion in one sibling. Whole exome sequencing revealed two rare variants including the novel variant p.Pro471Leu associated with NPC. Biochemical testing in both siblings confirmed the diagnosis of NPC, a treatable neurovisceral disease.